Incidence and Severity of Spodoptera frugiperda Attacks on Maize Crops in Kulon Progo District - Amalina Nadhilah Izzuddin; Putra, Ichsan Luqmana Indra (PLANTA TROPIKA, 2026)
Spodoptera frugiperda is a pest that can rapidly destroy maize plants and cause economic losses for maize farmers. The objective of this study was to analyze the incidence and severity of S. frugiperda on maize crops in Kulon Progo District. Sampling locations were determined using the random stratified method. The purposive method was used to determine the maize fields used for sampling. The W-scouting method was used to calculate the incidence and severity of S. frugiperda infestation. The collected data were analyzed using a correlation test to evaluate the relationship between the incidence and severity of S. frugiperda infestation. The analysis revealed spatial variability in infestation levels. The lowest incidence was observed in Samigaluh Sub-district, with an infestation rate of 9.13%, whereas the highest was observed in Panjatan Sub-district, with a rate of 20.95%. The degree of crop damage also differed among locations. In Lendah Sub-district, the pest caused substantial injury, with 14 corn plants categorized as severely damaged. In contrast, Temon Sub-district recorded 176 plants exhibiting only minor damage symptoms. These results indicate that S. frugiperda infestations were present throughout the surveyed region, with the highest incidence detected in Panjatan and the lowest in Samigaluh, suggesting localized differences in pest pressure and environmental suitability.